A review on the application of photocatalytic materials on textiles. Issue 10 (June 2015) - Wang, Jinfeng; Zhao, Jian; Sun, Lu; Wang, Xungai
Incorporation of functional additives is one of the most important ways of functionalizing textiles. Among the additives, photocatalyst has been used extensively in recent years. This paper reviews the current research status on application of photocatalysts in fibrous materials. The review concentrates on novel methods for coating various photocatalysts on textiles and properties of the photocatalyst-modified textiles. The fundamental limitations and future prospects of this research are also discussed.